2022
DOI: 10.1039/d2gc00073c
|View full text |Cite
|
Sign up to set email alerts
|

Construction of chevaux-de-frise from cellulose nanocrystals to enable mechano-bactericidal activity on recycled waste cotton films

Abstract: A chevaux-de-frise-like nanostructure is designed by depositing cellulose nanocrystals (CNCs) on regenerated cellulose (RC) films, both recycled from waste cotton fabrics, with the assistance of vacuum filtration to mechanically combat...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Therefore, the question of how to upcycle these low-value materials into value-added applications to address the growing concerns over sustainability and resource optimization has received tremendous attention [2,3]. So far, upcycling low-quality cotton fibers into dye adsorbents [4,5], composite paper [6], energy devices [7], and antibacterial agents [8] have been reported. However, these low-quality cotton fibers are still overlooked due to their perceived lack of economic viability.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the question of how to upcycle these low-value materials into value-added applications to address the growing concerns over sustainability and resource optimization has received tremendous attention [2,3]. So far, upcycling low-quality cotton fibers into dye adsorbents [4,5], composite paper [6], energy devices [7], and antibacterial agents [8] have been reported. However, these low-quality cotton fibers are still overlooked due to their perceived lack of economic viability.…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose comes from a wide range of sources such as plants and bacterias, so bioplastic derived from cellulose is considered to be of commercial potentials (Zhou et al, 2022). Heidarian et al reported a degradable composite made of cellulose extracted from sugarcane and PLA with the Young's modulus of 716.5 MPa, fracture strength of 32.6 MPa, and elongation at break of 4.5%, which degrades in more than two months (Heidarian et al, 2018).…”
Section: Introductionmentioning
confidence: 99%